Analysis of the Asymmetric Relationship between Oil Prices and Real Effective Exchange Rate in Kazakhstan - Abubakirova, Aktolkin; Kudabayeva, Lyazzat; Abdulina, Gulnar; Zurbayeva, Aliya; Tazhiyeva, Indira (International Journal of Energy Economics and Policy, 2021)
Kazakhstan’s export relies heavily on oil and other natural resources. Therefore, fluctuations in world oil prices have important consequences for Kazakhstan’s economy. The effect of fluctuations in oil prices on the real exchange rate is very important for economies trying to develop other sectors as well as oil and natural gas sectors such as Kazakhstan. The purpose of this study is to examine the possible asymmetric relationships between oil prices and real effective exchange rate in Kazakhstan for the period January 2010-December 2020. For this purpose, the asymmetric causality analysis method developed by Hatemi-J and Roca (2014) was used in the study. In the study, it was studied with monthly data for the period from January 2010 to December 2020. According to the results of the study, there is a causality relationship from negative oil price shocks to negative real effective exchange rate shocks in Kazakhstan. However, what is interesting is that a causality relationship from positive shocks in oil prices to real effective exchange rate could not be found. Keywords: oil price, Kazakhstan, real effective exchange rate, asymmetric relationship JEL Classifications: Q43; F41; C32 DOI: https://doi.org/10.32479/ijeep.11171